The Effect of Sponsorship Suitability on Music Festival Events - CHUSNAINI, AZMIL CHUSNAINI; RASYID, REIZANO AMRI (Universitas Nahdlatul Ulama Surabaya, 2023)
Sponsorship is the most important element in marketing communications for every type of company and organization among other types of marketing communications. Currently Sponsorship is believed to be one of the most powerful media used to link stakeholder relations communications to the target market. Sponsorship in the arts, especially music festivals, is one of the sponsorships that is more considered and can be used as a media promotion by many product brands because music is an industry that is highly developed and in great demand by the people of Indonesia. Therefore, this research is focused on contributing to the world of research, especially in the category of sponsorship activities in a music festival, by analyzing the influence of the EventSponsor suitability variable on Brand Image, Attitudes towards Sponsors, Attitudes towards Brands, and Purchase Intentions at Jazz music events Traffic Surabaya. This research is a quantitative study using a questionnaire distributed to 250 respondents. The results of the study explain that Event-Sponsor suitability has a positive effect on Brand Image, Attitudes have a positive effect on Sponsors, Attitudes towards Brands, and Purchase Intentions